Laparoscopy as A Diagnostic Tool In Elective Surgery: A Sir Ganga Ram Hospital Experience - A BILAL, SA SHAH M ARSHAD HU KHAN (Journal of Fatima Jinnah Medical University, 2018)
Objectives: This study was designed to evaluate the role of laparoscopy as a diagnostic tool in elective general surgical patients with obscure abdominal conditions. The preoperative working diagnosis was compared with the findings of diagnostic laparoscopy and the value of this modality was assessed in terms of its benefits and applicability. Study Design: A prospective randomized study Place and Duration of Study: Department of Surgery, Fatima Jinnah Medical College and Sir Ganga Ram Hospital Lahore. From July, 2009 to July, 2011. Subject / Methods: The study includes 60 patients that presented to the surgical outpatient department of Sir Ganga Ram Hospital with obscure abdominal conditions. These patients after thorough examination and provisional diagnosis were subjected to diagnostic laparoscopy under general anesthesia. Results: In all of the 60 patients included in the study the laparoscopy was successfully performed. The overall diagnostic accuracy of laparoscopy was 81.66 percent. In 65% of patients an unnecessary laparotomy was avoided. In about 16(26.6%) patients a decision in favor of a useful laparotomy was made. In 26(43.33%) patients laparoscopy helped in altering the course of management. The overall diagnostic efficacy turned out to be 86.6 percent. Conclusion: In this study it was concluded that laparoscopy is of great help in establishing the definitive diagnosis by inspection alone, or combined with biopsy. Laparoscopy is a reliable, safe and simple diagnostic procedure. The study proves that laparoscopy gave us larger latitude for decision making, wherever the diagnostic dilemma arose and it helps in avoiding unnecessary surgery or delay in surgery.